Corporate Governance and Board Effectiveness of Development Finance Institutions (DFIs) in the Southern African Development Community (SADC) Region - Pongaponga, Musonda Jonnah (Digital Repository of Theses, 2026)
This study investigates the impact of direct ministerial appointments on the governance and operational effectiveness of boards within Development Finance Institutions (DFIs) across the Southern African Development Community (SADC). While DFIs play a pivotal role in financing sustainable growth in the region, concerns persist over the extent to which politically driven appointments compromise governance quality, director independence, and institutional performance. The study’s central objective was to evaluate how ministerial interventions affect board effectiveness, ethical leadership, transparency, accountability, and composition, as well as to identify the challenges faced by directors operating within politically sensitive contexts. A mixed-methods research design was adopted, combining quantitative data from Likert- scale questionnaires with qualitative insights from open-ended responses. The analysis was framed by Agency Theory, Institutional Theory, Stewardship Theory, Resource Dependence Theory, and Stakeholder Theory. A total of 112 responses across seven research questions were examined. The findings show that although DFIs have formal governance structures in place, direct ministerial appointments weaken board independence, accountability, and the ethical stature of governance processes. Quantitative results revealed lower average scores for director independence (3.56/5) and resistance to political interference (3.42/5) compared with higher scores for ethical leadership (4.44/5) and transparency (4.53/5). Qualitative data corroborated these results, highlighting political interference, inadequate director training, limited board evaluations, and inconsistent selection criteria as major governance weaknesses. Respondents advocated the establishment of transparent and merit-based appointment mechanisms, reappointments linked to performance, and comprehensive capacity-building initiatives. The study concludes that safeguarding the developmental mandate of DFIs requires insulating governance structures from undue political influence. Transparent appointment mechanisms, meritocratic selection, and governance reforms that strengthen independence and accountability are critical. These findings generate policy-relevant insights for governments, regulators, and development partners within and beyond the SADC region. By providing empirical evidence from an under-explored area of DFI governance in the SADC region, this study contributes to the literature while offering practical guidance for policymakers and practitioners seeking to reinforce institutional governance frameworks. It further underscores the urgent need for regulatory reforms to align board appointments with the principles of ethical leadership, independence, accountability, and transparency, thereby enhancing overall board effectiveness.